The Role of the Personality Traits and Motivation in Manifestation in Pedagogues' Competencies - Papoyan, Varduhi; Galstyan, Alina; Sargsyan, Diana; Karapetyan, Milena (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The article presents the role of personality traits, personal qualities and motivation in the context of formation of the competences of pedagogues. The personality traits and the personal qualities which consider more stable characteristics of the person, as well as motivations which give direction to the person’s activity is also the basis for the formation of competencies of the person. The research was carried out by pedagogues from both community and city schools of the Republic of Armenia, with a total of 115 people. Of the data, the results of 99 respondents were valid.The study used a five-factor personality model, revealed the relationship of personal qualities with motivation. The analysis of the results showed that the main role of the formation and development of the competencies have such personality traits as Openness to experience, Agreeableness, Conscientiousness and Motivation. The motivation is absorbed as a satisfaction of the process and the result of the work, as well as the possibility of the most complete self-realization in this particular activity. The motivation is manifested when the activity of the pedagogue is of paramount importance for the individual.
Keywords: professional competencies; personal traits; motivation; personal qualities